Developmental stage variation in the gut microbiome of South China tigers - Zhang, Xianfu; Liao, Yanxin; Qin, Tao; Ma, Jinghua; Liu, Jianxun; Zou, Jianqiang; Huang, Haijun; Zhong, Xiaojun; Yang, Menghua (Frontiers in Microbiology, 2022)
South China tigers (Panthera tigris amoyensis, SC) are the most threatened tiger subspecies in the world. All the living SCs are captive in zoos or reserves and depend on artificial feeding. The composition of the gut microbiome plays an important role in sustaining the health of the host. A comprehensive understanding of the composition and development of the microbial community of SC is helpful to improve the feeding of captive SC. In this study, we collected 47 fecal samples, 37 of which were from SC of three developmental stages, 5 from adult Amur tigers (Am), and 5 from adult Bengal tigers (Bg), which were all housed in the same zoo. We investigated the diversity, richness, and composition of the bacterial microbiomes and we found that the gut microbiome of SC is strongly affected by host aging. The composition of the gut microbiome of juvenile SC experienced dramatic changes from 5 months old to one year old, and it showed much less difference when compared to the samples of one year old and the sub-adult. No significant differences were observed between the samples of subadult and the adult groups. The predominant phyla of 5-month-old SC is Fusobacteriota (33.99%), however, when the juvenile tigers were older than 5 months, Firmicutes but not Fusobacteriota became the predominant phyla of bacteria in their gut. The gut microbiome of SC, Am, or Bg is possibly affected by their genetic variation, however, the core microbiome of these three subspecies is the same. Our data suggest that the gut microbiome of SC undergoes a developmental progression: a developmental phase (cub), a transitional phase (subadult), and a stable phase (adult). These results expand our understanding of the role of age in the development of the gut microbiome of SC.